Acute Toxicities and Treatment tolerance of Neoadjuvant Chemoradiation in Rectal Cancer: A Tertiary Cancer Centre Analysis - Penumur, Manasa; Chanayil, Goutham Raj; Goswami, Smriti; Goswami, Bibhash Chandra; Paul, Moumita; Bora, Ghritashee (Asian Pacific Journal of Cancer Biology, 2024)
Background: To assess acute toxicities and treatment tolerance in patients with carcinoma rectum undergoing neoadjuvant chemoradiotherapy (NACTRT) at a tertiary care center in North-East India. Materials and Methods: A total of 50 patients with histologically proven rectal adenocarcinoma, recruited from July 2022 to May 2023, were included in the study. Patients were planned for either NACTRT (n=44) or total neoadjuvant treatment (TNT) (n=6) followed by surgical assessment. The treatment protocol included a total dose of 50.4 Gy delivered in 28 fractions with concurrent oral Capecitabine at a dose of 825 mg/m² twice daily. Acute toxicities were assessed using RTOG grading criteria. Toxicity assessments were performed weekly through clinical examination and laboratory tests, with additional evaluations at the end of radiotherapy and 4 weeks after completing NACTRT. Results: All patients completed the prescribed dose of external beam radiotherapy (EBRT) (50.4 Gy in 28 fractions) over a period of 6 weeks. Toxicity assessment revealed Grade 1 dermatitis in 14 patients (56%), Grade 2 dermatitis in 14 patients (54%), and Grade 3 dermatitis in 2 patients (7.6%). For lower gastrointestinal toxicities, Grade 1 diarrhea occurred in 4 patients (50%), Grade 2 diarrhea in 3 patients (37.5%), and Grade 3 diarrhea in 1 patient (7.6%). Grade 1 genitourinary toxicity was observed in 4 patients (8%). Hematological toxicities were reported in 40 patients, with Grade 1 anemia in 10 (38.4%), Grade 2 anemia in 14 (54%), and Grade 3 anemia in 2 (7.6%). Grade 1 and Grade 2 leucopenia were observed in 4 (57%) and 3 (43%) patients, respectively. Liver function test abnormalities were noted in 7 patients (15%), with dose modifications required for 5 patients (10%). Treatment was temporarily put on hold for 3 patients (6%) for 3 days due to Grade 3 toxicities. Conclusion: NACTRT in rectal cancer patients was associated with acceptable levels of toxicity and treatment tolerance. To further reduce radiation-related toxicities, modern external beam radiotherapy techniques, such as intensity-modulated radiotherapy (IMRT), should be evaluated.